Report on the CLIMBER Work Package 3 Technical Working Group 1st Virtual Meeting - Whitfield, Stephen; Sarku, Rebecca; Mavuso, Terrence; Nkanyani, Shiluva Chauke; Laichena, Joshua (CGIAR System Organization, 2024)
THIS IS REPORT ON THE CLIMBER WORK PACKAGE 3 TECHNICAL WORKING GROUP 1ST VIRTUAL MEETING. Without adaptation solutions now, millions of smallholder farmers will be unprepared for the severe consequences of increased temperature, drought, flooding, and other climate extremes. Building Systemic Resilience Against Climate Variability and Extremes, or CLIMBER, is a CGIAR Research Initiative that will address this challenge as part of CGIAR’s new research portfolio that will deliver science and innovation to transform food, land, and water systems.T he Food, Agriculture and Natural Resources Policy Analysis Network (FANRPAN) and the Kenya Institute for Public Policy Research and Analysis (KIPPRA) coordinate work in Kenya under CLIMBER Work Package 3, along with CGIAR institutions and partner organisations from the UK.